Diagnostic accuracy of p16INK4a immunohistochemistry in oropharyngeal squamous cell carcinomas: a systematic review and meta-analysis - Prigge, Elena-Sophie; Knebel Doeberitz, Magnus von; Reuschenbach, Miriam (International journal of cancer, 2017)
The accurate diagnosis of human papillomavirus (HPV) causality in oropharyngeal squamous cell carcinomas (OPSCC) is likely to influence therapeutic decisions in affected patients in the near future. We conducted a systematic review and meta-analysis to determine the diagnostic accuracy of p16INK4a immunohistochemistry (IHC) to identify HPV-induced OPSCC. We identified all studies that performed p16INK4a IHC (index test) and HPV E6/E7 mRNA detection using an amplification-based method (gold standard to indicate a transforming relevance of HPV) in OPSCC. Testing with one or more comparator tests (HPV DNA PCR, HPV DNA in situ hybridization (ISH) and p16INK4a IHC/HPV DNA PCR combined testing) was an optional criterion for inclusion. Among 1,636 retrieved studies 24 fulfilled the inclusion criteria. The pooled sensitivity of p16INK4a IHC, HPV DNA PCR, HPV DNA ISH and p16INK4a IHC/HPV DNA PCR combined testing was 94% (95%-confidence interval (CI) 91-97%), 98% (CI 94-100%), 85% (CI 76-92%) and 93% (CI 87-97%), respectively. The pooled specificity was 83% (CI 78-88%), 84% (CI 74-92%), 88% (CI 78-96%) and 96% (CI 89-100%), respectively. p16INK4a IHC/HPV DNA PCR combined testing was as sensitive as either p16INK4a IHC or HPV DNA PCR alone but significantly more specific than either separate test. In conclusion, p16INK4a IHC is highly sensitive but moderately specific to diagnose HPV-transformed OPSCC when used as a single test. Combined p16INK4a IHC and HPV DNA PCR testing significantly enhances specificity while maintaining high sensitivity. This diagnostic test combination thus represents an attractive testing strategy for the reliable diagnosis of HPV-induced OPSCC in the clinical setting and may constitute an inclusion criterion for future therapeutic trials.